Cryopreservation-related loss of antigen-specific IFNγ producing CD4+ T-cells can skew immunogenicity data in vaccine trials: Lessons from a malaria vaccine trial substudy. Issue 15 (4th April 2017) - Ford, Tom; Wenden, Claire; Mbekeani, Alison; Dally, Len; Cox, Josephine H.; Morin, Merribeth; Winstone, Nicola; Hill, Adrian V.S.; Gilmour, Jill; Ewer, Katie J.
Abstract: Ex vivo functional immunoassays such as ELISpot and intracellular cytokine staining (ICS) by flow cytometry are crucial tools in vaccine development both in the identification of novel immunogenic targets and in the immunological assessment of samples from clinical trials. Cryopreservation and subsequent thawing of PBMCs via validated processes has become a mainstay of clinical trials due to processing restrictions inherent in the disparate location and capacity of trial centres, and also in the need to standardize biological assays at central testing facilities. Logistical and financial requirement to batch process samples from multiple study timepoints are also key. We used ELISpot and ICS assays to assess antigen-specific immunogenicity in blood samples taken from subjects enrolled in a phase II malaria heterologous prime-boost vaccine trial and showed that the freeze thaw process can result in a 3–5-fold reduction of malaria antigen-specific IFNγ-producing CD3 + CD4 + effector populations from PBMC samples taken post vaccination. We have also demonstrated that peptide responsive CD8 + T cells are relatively unaffected, as well as CD4 + T cell populations that do not produce IFNγ. These findings contribute to a growing body of data that could be consolidated and synthesised as guidelines for clinical trials with the aim of increasing the efficiency of vaccine development pipelines.